Ética Performada, Arracachas Al Poder. Innovar desde la filosofía y las artes con un semillero performativo de investigación - Sarmiento-Zárate, Rafael Eduardo (Educación y Ciudad, 2019)
The present document exposes the classroom project "Performed ethics - arracachas al poder", which arose in 2010 with the teacher's autoethnography, in the School José Francisco Socarras de Bosa. Integrating coherently the teacher's biography with the dynamics of the ethics, philosophy and political science classes, proposing an innovative methodology that integrates them with arts, especially the scenic and / or audiovisual ones. Since 2015 until now at days, the experience has been enriched with the creation of a performative research center called Arracachas al Poder.